Temporary Prohibition of Tiktok Shops from a Pancasila Perspective - Razali, Geofakta; Syahri, Syahri; Thamrin, Andi; Kalalo, Rieneke Ryke; Wibisono, Okki Navarone (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Pelarangan sementara Tiktok Shop oleh pemeerintah bertujuan untuk menjaga kesenjangan pendapatan antara pedagang online dan pedagang offline agar tidak terjadi kesenjangan sosial. Penelitian ini merupakan penelitian Kualitatif dengan pendekatan Deskriptif. Data yang digunakan dalam penelitian ini meruppakan data sekunder. Data yang didaptkan tersebut dinalisis dengan tahapan pengumpulan data, seleksi data, reduksi data, dan pernarikan kesimpulan. Hasil penelitian menunjukkan 1). The ban on Tiktok shops by the Indonesian government is due to unhealthy competition because Tiktok shops are not pure e-commerce but are also social media, prices are unreasonable, large quantities of imported goods, and so on which only benefit a handful of parties. 2). The government's aim is to ban Tiktok shops so that demand and supply in offline shops remains stable and MSMEs, which are the heart of the Indonesian economy, do not die. 3). The prohibition carried out by the government is in line with the fifth principle of Pancasila values, specifically emphasizing justice and equal distribution of income for offline traders and MSMEs.